Effective Communication Skills of University Students Studying in Different Departments: The Role of Participation in Activities - Cengiz BAYRAKTAR; Esranur TERZİ; Berat Can İNAN; Can AKYILDIZ; Ersen BAKIRHAN (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
The aim of this study is to investigate the level of communication skills among university students and determine whether participation in activities affects communication skills. The study included a total of 398 university students, selected through random sampling, with an average age of 23.86 ± 5.10. Data for the research were collected through an online survey using the "Personal Information Form" and the "Effective Communication Skills Scale." Normality tests were conducted for the data, and One Way MANOVA analysis was used for comparisons of data found to have a normal distribution. Additionally, Pearson Correlation test was employed to examine the relationship between continuous variables. The analysis revealed that university students' effective communication skills differed based on gender, age, faculty, and participation in various activities (p < 0.05). In contrast to the literature, our study found that the concept of effective communication skills, examined in a sample of university students studying in various faculties, not only varied among faculties but also was influenced by factors such as gender, age, and participation in various activities. In conclusion, the study determined that women are more sensitive in establishing effective communication, maturity with age brings changes in communication skills, students whose future professions involve direct interactions with people are more sensitive to effective communication, and participation in various activities enhances communication skills by socializing individuals.